Abstracts 2018
DOI: 10.1136/injuryprevention-2018-safety.458
|View full text |Cite
|
Sign up to set email alerts
|

PW 0413 Prevalence and nature of trauma and injuries in karachi. National trauma registry of pakistan ‘the need of the hour’

Abstract: ObjectiveTo assess the prevalence, nature of trauma, reason(s) behind these trauma and first-aid care provided during transportation to hospital in Karachi Pakistan. Study also presents the framework of a national trauma registry and comparatively analyzes data between other registries.MethodThis cross sectional observational/descriptive study was conducted from July 2015 to Dec 2015. An informed verbal consent was taken and preformed questionnaire was filled. Patient brought dead and who did not give consent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…11 A similar study conducted in Karachi Pakistan for the prevalence and nature of trauma revealed most common age group involved was 11-20 years, most of whom were student by occupation and motorcyclist followed by pedestrians 12 ; the present study also emphasises improvement in trauma care depends on the establishment of on functioning trauma care systems most importantly trauma training and establishment of trauma registry. 12 Global injury report statistics show that 85% of all RTA deaths in the world occur in countries of low and middle income and the rapidly increasing number of vehicles in these regions will contribute to a rise of 80% more mortality and fatality rates between 2000 and 2020. 13 A study by Reynolds et al, 14 elucidates that basic training of emergency healthcare provider is the cornerstone in trauma management in any setup and this factor is weak in these regions and therefore have a critical impact on trauma care systems in developing countries.…”
Section: Discussionsupporting
confidence: 62%
“…11 A similar study conducted in Karachi Pakistan for the prevalence and nature of trauma revealed most common age group involved was 11-20 years, most of whom were student by occupation and motorcyclist followed by pedestrians 12 ; the present study also emphasises improvement in trauma care depends on the establishment of on functioning trauma care systems most importantly trauma training and establishment of trauma registry. 12 Global injury report statistics show that 85% of all RTA deaths in the world occur in countries of low and middle income and the rapidly increasing number of vehicles in these regions will contribute to a rise of 80% more mortality and fatality rates between 2000 and 2020. 13 A study by Reynolds et al, 14 elucidates that basic training of emergency healthcare provider is the cornerstone in trauma management in any setup and this factor is weak in these regions and therefore have a critical impact on trauma care systems in developing countries.…”
Section: Discussionsupporting
confidence: 62%
“…In our six-month data for a trauma registry, the highest number of injuries were attributed to motorcycle crashes (22%). 8 Given the smaller size of the motorcycle occupying a smaller area in the visual field, distracted drivers may have poorer reaction times as compared to motorcars.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to our previous data recorded in the same hospital, the most common injury was femur fractures (10%). 8 This can be explained by the lower speed of vehicles involved in distracted driving. Data from the United States reports that drivers actively using a cell phone have a higher chance of driving slower, mimicking congested traffic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations